Proso Millet and Phalaris as Alternatives for Wheat Flour in Preparing Balady Bread - Azza, A. Omran; Zahrat El-Ola, M. Mohamed; Ghada, A. Alfauomy (Food Technology Research Journal)
The influence of partial substitution of wheat flour (87.50% extraction) with proso millet or phalaris flour in balady bread blends, and their effects on bread quality were studied to meet the need for alternative sources for making balady bread suitable for Egyptian consumers. Wheat flour blends were prepared with different substitution levels (10–25%) of proso millet or phalaris flour and used for preparing balady bread. Proximate analysis for raw materials and rheological analysis for the blends were evaluated. Balady bread was examined for sensory evaluation, proximate analysis, color, and staling. The highest contents of protein, ash, fat, fibers, zinc, phenols, carotenoids, antioxidant activity, and water holding capacity were found in phalaris flour, while proso millet flour had a higher iron content and oil holding capacity. Regarding rheological analysis, the water absorption of dough declined as proso millet ratios increased; however, it elevated with increasing phalaris ratios. Substituting wheat flour with proso millet or phalaris flour in the balady bread resulted in an increase in protein, fat, crude fibers, phenols, and carotenoids contents relative to the control bread, as well as antioxidant activity. Likewise, there is an increase in the weight and yellowness of the produced bread with increasing levels of proso millet substitution. The best overall acceptability of the resulting balady bread was achieved by substituting wheat flour with 15% proso millet or 10% phalaris flour, respectively.